Ἀπὸ τὴ μνήμη γιὰ τὸν πόλεμο στὸν πόλεμο γιὰ τὴ μνήμη - ΤΕΝΕΚΕΤΖΗΣ ΑΛΕΞΑΝΔΡΟΣ Ν. (Μνήμων, 2011)
The experience of the 20th century changed forever the relationship which societies and individuals had with their past. Memory, or rather the historical memory, is a reality, a process, which includes works of art as well. The memory of the Second World War, its construction, reproduction, and representation, was expanded dramatically during the postwar era and played an important role in the social and political life. What had began as a common experience transformed quickly, within the context of Cold War, into a conflict over memory, a conflict with different causes, different aspirations and different goals; a coflict over the character and content of this memory, a conflict for the dominance of one memory over another, which finally would take an artistic form as well. The plurality of the artistic expression in the public monumental practice confirms the substantial divergence of the interpretation of the war between different social and ethnic groups in the divided European Continent.